The Potency of UB Forest Bacteria as Chitinolytic Bacteria to Inhibit Anthracnose Disease on Cayenne Pepper - Nava Karina; Achmad Roekhan; Cindy Diah Ayu Fitriana; Luqman Qurata Aini (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2020)
Anthracnose disease is a major disease in cayenne pepper triggered by fungal pathogen Colletotrichum capsici which can cause yield losses of up to 90%. Control of disease generally utilizes synthetic fungicides, but it damages the environment and human health. Hence, alternative controls that are ecofriendly are required. One of the attempts is to make use of chitinolytic bacteria's potential. This study aimed to screen UB Forest chitinolytic bacteria and to determine their potential in suppressing anthracnose in cayenne pepper. Stages of research include a screening of 78 UB Forest bacteria as chitinolytic bacteria, selection of chitinolytic bacteria that are antagonistic against C. capsici, inhibition test of chitinase crude extracts against C. capsici growth, controlling anthracnose disease in cayenne using chitinolytic bacteria, and molecular identification. Based on the results of the selection, there were 76 isolates of UB Forest bacteria classified as chitinolytic bacteria, 74 bacteria antagonistic against C. capsici. Chitinase crude extracts significantly affected C. capsici growth inhibition compared to fungicide treatment. The application of Pseudomonas aeruginosa (UB 11) and Bacillus cereus (UB 12) can control anthracnose disease in cayenne pepper with the intensity of 41.67% and 38.89% respectively with the efficacy level of 58.33% and 61.11%.